Islamic Boarding School Management in Forming The Religious Character of Students - Moh Komarodin; Ainur Rofiq (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2023)
Education has a very strong position in preparing humans to live perfectly and happily. Coaching and monitoring for 24 hours for students is carried out by the Al-Hajar Karemejo Islamic Boarding School which is aimed at fostering their personality. This study aims to: 1) Explain the planning of Islamic boarding schools in improving the religious character of students, 2) Describe the management of Islamic boarding schools in improving the religious character of students, 3) Describe the supervision of Islamic boarding schools in improving the religious character of students, 4) Describe the evaluation of Islamic boarding schools in improving the character of Islamic boarding schools. religious students. The type of research used in this research is qualitative research with a case study approach and the data collection techniques used are observation, documentation, and interviews. The results of this study include 1) Islamic boarding school planning in improving the religious character of students, 2) Management of Islamic boarding schools in improving the religious character of students, 3) Supervision of Islamic boarding schools in improving the religious character of students, 4) Evaluation of Islamic boarding schools in improving the religious character of students.